Penerapan Model Pembelajaran Kooperatif Tipe Student Facilitator And Explaining (SFaE) Berbantuan Media Powerpoint Pada Materi Statistika Di Kelas VIII MTS Darul Ulum Karang Pandan - Isnaini, Novi; Sari, Mayang (Allimna: Jurnal Pendidikan Profesi Guru, 2022)
This study aims to describe the management of learning, student activity, student learning outcomes, and student responses to learning with the Student Facilitator and Explaining (SFAE) type cooperative learning model assisted by PowerPoint media on statistics material in class VIII-A MTs Darul Ulum Karang Pandan. This research is a descriptive qualitative research. The subjects of this study were researchers who acted as teachers and students of class VIII-A MTs Darul Ulum Karang Pandan for the 2021-2022 academic year. 8 students were randomly selected from class VIII-A as the subject of observing student activity. Data collection was carried out during 2 meetings for learning with the Student Facilitator and Explaining (SFAE) cooperative learning model assisted by PowerPoint media, and 1 meeting for learning achievement tests and student response questionnaires. During learning, observations were made on the management of learning, and student activities. The results of the data analysis show that the management of learning by the teacher as a whole can be categorized as good, student activity while participating in learning is classified as active with the percentage of student activity being 63.28%, student learning outcomes with an average of 82.73, and student responses to learning using Student Facilitator And Explaining (SFAE) type learning assisted by PowerPoint media is positive.